Les Gilets jaunes : « nous sommes le peuple » - Eric Puisais (Amnis)
Much has been written about the Gilets jaunes movement. Politicians and social scientists alike have produced analyses and shared their views. Is there any point in adding more? This article is not intended as a review of the literature on the subject, but rather as a theoretical observation of the movement and a reflection on the contemporary evolution of the notion of the people in different conceptions of democracy. The aspirations of the Gilets jaunes, like the political response they have received, draw a distinction that reveals a profound crisis in politics.